Antimicrobial efficacy of silver nanoparticles with and without different antimicrobial agents against Enterococcus faecalis and Candida albicans - Anil Chandra; Rakesh K Yadav; Vijay K Shakya; Suaib Luqman; Simith Yadav (Wolters Kluwer Medknow Publications, 2017)
Introduction: The aim of this ex vivo study was to check the antimicrobial efficacy of silver nanoparticles with and without different antimicrobials against Enterococcus faecalis and Candida albicans. Materials and Methods: Two-hundred and fifty two freshly extracted single-rooted human teeth were contaminated with E. faecalis and C. albicans. The teeth were randomly divided into five experimental (n = 21) and one control group (n = 21). Each subgroup was then exposed to different antimicrobials, namely calcium hydroxide (Ca(OH)2) (Group 1), 2% chlorhexidine (CHX) (Group 2), silver nanoparticles (SNP) (Group 3), SNP with Ca(OH)2 (Group 4), SNP with 2% CHX (Group 5), and saline as control group (Group 6). Cultures were made from each group after 24 h, 7 days, and 14 days, and colony forming units were counted. The Kruskal-Wallis test was used to compare the study parameters among the groups at 24 h, 7 days, and 14 days. Results: Significant difference was found in the antimicrobial efficacy of different intracanal medicaments against E. faecalis and C. albicans after 24 h, 7 days, and 14 days. 2% CHX was found to be the most effective medicament at 24 h, 7 days, and 14 days against E. faecalis and C. albicans. Combination of SNP with 2% CHX and Ca(OH)2 and SNP alone ranked second in their antimicrobial efficacy against E. faecalis and C. albicans at 24 h, 7 days, and 14 days, respectively. Conclusion: 2% CHX was more effective as intracanal medicament against E. faecalis and C. albicans biofilm in both short as well as long-term duration, i.e., at 24 h, 7 days, and 14 days.